The curious world of Samuel Pepys and John Evelyn - Willes, Margaret (Yale University Press, 2017)
"Samuel Pepys and John Evelyn vividly reveal in their diaries and correspondence the world of Restoration England. Now Margaret Willes uses the analogy of a cabinet of curiosities to provide a detailed account not only of the two friends but also of their times. Pepys was down to earth and realistic, while Evelyn was a genteel aesthete, but, brought together by their work to help distressed sailors, they developed a long and close friendship. This was enriched by their mutual interest in all aspects of science, in travel and exploration at a time when the known world was rapidly expanding, and their love of books. Above all, they shared an inexhaustible curiosity. Both were on personal terms with the King and his ministers, and leading figures of the scientific, artistic and mercantile communities, so that they provide a very personal portrait of a friendship sustained through a time of war, catastrophe and revolution."--Provided by publisher